Biomechanical analysis and clinical effects of bridge combined fixation system for femoral fractures. (September 2014) - Wang, Da-xing; Xiong, Ying; Deng, Hong; Jia, Fu; Gu, Shao; Liu, Bai-lian; Li, Qun-hui; Pu, Qi; Zhang, Zhong-zi
This work aimed to compare the stress distribution and mechanical properties of our bridge combined fixation system and commonly used metal locking plate screw system by finite element analysis and by using the Zwick/Z100 testing machine. In addition, we also investigated the clinical outcome of our bridge combined fixation system for femoral fractures in 59 patients from June 2005 to January 2013. As a result, the stress distribution in the bone plate and screws of metal locking plate screw system during walking and climbing stairs was significantly lower than that of metal locking plate screw system. No significant difference in the displacement was observed between two systems. The equivalent bending stiffness of bridge combined fixation system was significantly lower than that of metal locking plate screw system. There were no significant differences in the bending strength, yield load, and maximum force between two systems. All the cases were followed up for 12–24 months (average 18 months). The X-ray showed bone callus was formed in most patients after 3 months, and the fracture line was faint and disappeared at 6–9 months postoperatively. No serious complications, such as implant breakage and wound infection, occurred postoperatively. According to self-developed standard for bone healing, clinical outcomes were rated as excellent or good in 55 out of 59 patients (success rate: 93.2%). Therefore, our findings suggest that our bridge combined fixation system may be a promising approach for treatment of long-bone fractures.